2021
DOI: 10.1007/s10704-020-00510-x
|View full text |Cite
|
Sign up to set email alerts
|

Phase-field modelling: effect of an interface crack on precipitation kinetics in a multi-phase microstructure

Abstract: Premature failures in metals can arise from the local reduction of the fracture toughness when brittle phases precipitate. Precipitation can be enhanced at the grain and phase boundaries and be promoted by stress concentration causing a shift of the terminal solid solubility. This paper provides the description of a model to predict stress-induced precipitation along phase interfaces in one-phase and two-phase metals. A phase-field approach is employed to describe the microstructural evolution. The combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…It can be seen that the thickness of the lamellar phase grains decreases in the NFR, and the lamellar α phase grains exhibit shear deformation, as indicated by the white circles. Previous investigations have found that the parallel arrangement of α/β phase boundaries is prone to be a source of crack initiation [23], and the crack would expand rapidly along the direction perpendicular to the lamellar α phase grains [24]. This is one of the key reasons for the poor plasticity of the LM alloy.…”
Section: Features Of the Deformation Microstructurementioning
confidence: 99%
“…It can be seen that the thickness of the lamellar phase grains decreases in the NFR, and the lamellar α phase grains exhibit shear deformation, as indicated by the white circles. Previous investigations have found that the parallel arrangement of α/β phase boundaries is prone to be a source of crack initiation [23], and the crack would expand rapidly along the direction perpendicular to the lamellar α phase grains [24]. This is one of the key reasons for the poor plasticity of the LM alloy.…”
Section: Features Of the Deformation Microstructurementioning
confidence: 99%